2016
DOI: 10.1007/s00330-016-4473-5
|View full text |Cite
|
Sign up to set email alerts
|

Injury patterns of medial patellofemoral ligament after acute lateral patellar dislocation in children: Correlation analysis with anatomical variants and articular cartilage lesion of the patella

Abstract: • MPFL is most easily injured at its patellar insertion in children. • Wiberg patellar type B predisposes to complete MPFL tear. • No correlations between injury patterns of MPFL and other three anatomical variants. • Complete MPFL tear predisposes to higher grade patellar chondral lesion. • No correlations between injury locations of MPFL and patellar cartilage lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 60 publications
4
28
0
Order By: Relevance
“…More recent studies in the adult and aged-mixed populations have reported a variety of multifocal, central, or patellar attachment injuries; the majority of the lesions were at the patellar attachment site in the younger population. 47,83,140,147,157,183 It is important to know the location and severity of the MPFL injury in the treatment decisions for traumatic LPD.…”
Section: Mpflmentioning
confidence: 99%
“…More recent studies in the adult and aged-mixed populations have reported a variety of multifocal, central, or patellar attachment injuries; the majority of the lesions were at the patellar attachment site in the younger population. 47,83,140,147,157,183 It is important to know the location and severity of the MPFL injury in the treatment decisions for traumatic LPD.…”
Section: Mpflmentioning
confidence: 99%
“…Patients were eligible for inclusion if they had suffered an acute, first-time LPD regardless of the injury mechanism. The inclusion criteria were as follows ( 17 18 19 20 21 ):…”
Section: Methodsmentioning
confidence: 99%
“…Using the diagnostic classification criteria from studies of Zhang et al and Balcarek et al ( 17 18 19 20 21 22 23 24 ), the degrees of MPFL injury were divided into partial and complete tears. The manifestations of a partial MPFL tear were defined as thickening and irregularity of the contour, including discontinuity of normal fibers, and intraligamentous or extensive periligamentous edema.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The MPFL site of injury appears multifocal, and thus, repair depends on accurate diagnosis of the location of injury. A magnetic resonance imaging study by Zhang et al 5 looked at the site of MPFL injury in pediatric patients and concluded that isolated femoral avulsion occurred in 32%, isolated patellar avulsion occurred in 39% and ligament stretch occurred in 4%; however, in 25%, there was more than 1 site of injury. Askenberger et al 6 also looked at injury sites of the MPFL after patellar dislocation, and although the results showed a preponderance of patellar avulsions, they found that 35% of patients had a multifocal injury.…”
Section: See Related Article On Page 2909mentioning
confidence: 99%